2017
DOI: 10.1111/jgs.15225
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change in Cognitive Status Classification of Black Older Adults

Abstract: OBJECTIVES:The purpose of this study was to determine whether stability and change in cognitive status are associated with sociodemographic characteristics and health function. DESIGN: Secondary analysis of data. SETTING: Baltimore Study of Black Aging-Patterns of Cognitive Aging. PARTICIPANTS: Community-dwelling black adults (N = 407; mean age 68.6 AE 9.1). MEASUREMENTS: Baseline (n = 602) and 33-month follow-up (n = 450) assessments of cognition, health, and psychosocial function. RESULTS: For the present an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…A total of 1610 articles in English were screened, of which 17 were selected and included according to the established search strategy (Table S1). The total number of subjects was 6829, of which 1883 were reverted, amounting to an overall reversion rate of 27.57%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1610 articles in English were screened, of which 17 were selected and included according to the established search strategy (Table S1). The total number of subjects was 6829, of which 1883 were reverted, amounting to an overall reversion rate of 27.57%.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing body of evidence suggests that being an APOE ε4 carrier is a risk factor for AD and the progression of MCI to AD . APOE is closely related to the status and stability of MCI .…”
Section: Disscusionmentioning
confidence: 99%
“…Research using such screeners demonstrated that measures of executive functioning, immediate, and delayed recall had adequate sensitivity and specificity to provide useful information to healthcare providers (Cameron et al, 2016). Overall, when researchers control for group differences in health, differences in performance between ethnoracial minorities and non-Hispanic Whites can be attenuated (Aiken-Morgan et al, 2018; Jones, 2003). Another way to minimize group differences is to estimate mean performance by freely estimating the intercepts for different ethnoracial groups (Avila et al, 2020).…”
Section: Identifying Subgroups Of Ethnoracial Minorities: What Is Los...mentioning
confidence: 99%
“…Based on previous studies [6,11,[26][27][28], demographic characteristics included age (years), residence (urban/ rural), marital status (married/divorced/single), education (illiterate/primary school/middle school and above) and health insurance status (yes/no). Lifestyle behaviors including smoking status (current/former/never), alcohol use (current/former/never) and social activity (none/inactive/active) were also taken into consideration.…”
Section: Covariate Assessmentmentioning
confidence: 99%